2018
DOI: 10.1016/j.cobeha.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for the greater good: neural mechanisms of overcoming costs

Abstract: To obtain greater goods decision makers often have to incur and endure costs. Here we review mechanisms that enhance the willingness to accept and overcome costs in individual and social settings. General, cost-invariant mechanisms involve controlling and reducing reward-related impulsivity, abstracting from personal and situational circumstances, changing the availability of options in the choice set, and reinterpreting aspects of the choice alternatives. These mechanisms are based on fronto-striatal and fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…With regard to attention and arousal, we also found indications that anticipatory activity in the LC increased as a function of incentive magnitude. This would suggest a role for noradrenergic influences, potentially increasing arousal, attention or motivation to overcome effort costs (Aston-Jones and Cohen, 2005; Soutschek and Tobler, 2018; Walton and Bouret, 2018). However, the LC is a challenging area to image with fMRI (Liu et al , 2017) and our imaging sequence was not optimized to detect signals in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to attention and arousal, we also found indications that anticipatory activity in the LC increased as a function of incentive magnitude. This would suggest a role for noradrenergic influences, potentially increasing arousal, attention or motivation to overcome effort costs (Aston-Jones and Cohen, 2005; Soutschek and Tobler, 2018; Walton and Bouret, 2018). However, the LC is a challenging area to image with fMRI (Liu et al , 2017) and our imaging sequence was not optimized to detect signals in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Their strength lies in repetition, stability, and error avoidance using strategies of conservation, goal maintenance, and maintaining the status quo (Van Dijk & Kluger, 2011). Because helping customers, providing feedback, and offering recommendations all involve certain risks (Calo, 2008; Soutschek & Tobler, 2018; Van Dyne & LePine, 1998), compared to promotion‐focused ones, prevention‐focused individuals rarely communicate and exchange thoughts and ideas with others in order to avoid associated risks. Accordingly, they are less likely to engage in CCB.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Social discounting (the decline in the subjective value of a reward as a function of increasing social distance to its recipient) is thought to be related to delay discounting, the decline in the subjective value of a reward as a function of increasing temporal distance to its receipt (Ainslie, 2005;Berns et al, 2007;Kable, 2014;Loewenstein & Elster, 1992). Both phenomena reflect valuebased decision-making that requires weighing up costs and benefits between the present self and other beneficiaries (socially distant individuals or temporally distant selves; Berkman et al, 2017;Buckholtz, 2015;Soutschek & Tobler, 2018) and thus both involve psychological distance in addition to perspective taking. The steepness of social discounting and delay discounting rates have been shown to be associated across individuals (Jones & Rachlin, 2009) and neuroimaging studies have revealed evidence of partially overlapping neural correlates (Hill, Spreng & Diana, 2017;Soutschek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%